Narrative, Identity and Terrorism: A Constructivist Analysis of the Pahalgam 2025 Attack in the Escalating India–Pakistan Conflict - Neola Hestu Prayogo; Dewi Fortuna Sari (WIMAYA, 2025)
The terrorist assault on Pahalgam in 2025 signified a new chapter in the enduring conflict between India and Pakistan. This study analyses how the governments of both nations produced official narratives in reaction to the occurrence and how these narratives embody and promote their distinct national identities. The research used a constructivist method to examine the production of identity and meaning through political speeches, government pronouncements, and media framing. The analysis relies on qualitative interpretation of secondary sources, such as diplomatic briefings, ministerial speeches, and reports from esteemed foreign media sites. Evidence suggests that India characterized the assault as an instance of cross-border terrorism, supporting its self-perception as a secular and democratic nation under threat and justifying retaliatory measures. Pakistan, in response, dismissed the claims and sought to recast the episode as a contrived crisis intended to divert attention from Indian persecution in Kashmir, portraying itself as a victim rather than an aggressor. This study illustrates that identity formation and story creation are essential strategies in perpetuating the competition between India and Pakistan, distinguishing this research from earlier studies mainly concentrating on strategic, legal, or security aspects. It contends that absent a shift in one state's perception and representation of the other, future crises will likely follow analogous discursive patterns.